(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This article tries to reflect on perceptions of the term ‘Environment’ in relation to Art practices in India. It tries to find a connection between visual Art and material environment. My explorations would be through monumental sculptures and murals in public domain. At this time of Global warming and ecological crisis, we no longer think of Art in isolation. Hence it is a challenge for a visual artist to negotiate of ‘how to use materials in a way that is creative as well as environment friendly’ or ‘to create Art out of waste’. This means, using things that are thrown away to create awareness among the people that nothing in nature is waste. In this article, I will highlight some public sculptures made out of industrial waste which were laying in the corporation scrapyard for so many years and how artist community took it as a challenge and created beautiful pieces of Art out of them. Through these artworks, they also tried to create an awareness about conservation of energy, conservation of our cultural heritage and awareness about art in general and at the same time giving the cities an individuality and unique character. It also explores the street art of Dharavi where Art has transformed the place from gloomy to happiness and Delhi’s Lodhi Street Art where art is used as a powerful tool of mass communication.